0139 Associations of Actigraphic Sleep Parameters with Maximal Oxygen Consumption and Resting Metabolism in Well-Functioning Older Adults. (27th May 2020) - Alfini, A J; Wanigatunga, A A; Schrack, J A; Wanigatunga, S; Li, J; Rojo-Wissar, D M; Mehta, R; Okoye, S; Zipunnikov, V; Simonsick, E M; Spira, A P
Abstract: Introduction: Both poor sleep and poor cardiorespiratory fitness are common in older age and associated with negative health outcomes. Additionally, among older adults, higher resting metabolic rate (RMR) has been associated with increased morbidity and mortality risk. To evaluate whether, and in what ways, sleep may affect these relationships, we investigated the association of actigraphic sleep indices with cardiorespiratory fitness and RMR in older adults. Methods: We studied 393 community-dwelling participants in the Baltimore Longitudinal Study of Aging (mean age 73.5±10.3 years, 52% women) who completed 6.7±0.9 nights of wrist actigraphy, RMR testing, and a maximal graded exercise test. Primary predictors included mean actigraphic total sleep time (TST, minutes), sleep efficiency (SE, %), wake after sleep onset (WASO, minutes), and average wake bout length (WBL, minutes). Cardiorespiratory fitness, as measured by maximal oxygen consumption (V O2MAX ; ml/kg/min), and RMR (kcal/day) were the primary outcomes. Results: After adjustment for age, sex, race, body mass index, comorbidity index, and depressive symptoms, longer WBL was associated with lower V O2MAX (β=-0.12, 95% confidence interval (CI)=-0.20, -0.04), greater WASO was associated with lower V O2MAX (β=-0.09, 95% CI=-0.17, -0.01), and greater SE was associated with higher V O2MAX (β=0.12, 95% CI=0.03, 0.20). In addition, longer TST was associated with lower RMR (β=-0.10, 95% CI=-0.19, -0.01) and longer WBL was linked to higher RMR (β=0.12, 95% CI=0.04, 0.21). Conclusion: In well-functioning older adults, indices of greater wakefulness after sleep onset are linked with poorer cardiorespiratory fitness and higher resting metabolism, while longer and more efficient sleep are associated with better fitness and lower resting metabolic rate. Our findings suggest that sleep disturbance may be linked to disrupted energy homeostasis, evidenced by excessive energy expenditure at rest and inefficient energy utilization in response to maximal demands. Prospective analyses are necessary to determine the nature of these associations. Support: This study was supported in part by National Institute on Aging (NIA) grants R01AG050507 and T32-AG027668, the NIA Intramural Research Program (IRP), and Research and Development Contract HHSN-260-2004-00012C.